(untitled) (Research, Society and Development, 2017)
The objective of this study is to investigate the conditions of access and permanence of people with disabilities in higher education. A descriptive research methodology with a qualitative approach was used, through a review accomplished with mapping of academic publications produced in the period 2008-2015. The preference of this periodization was due to relevant norms in the discussion of subject: the "National Policy of Special Education in the Perspective of Inclusive Education" of 2008 and the “Statute of the Person with Disabilities” of 2015. In the persuit for literature, we used the keywords "inclusion", "deficiency" and "higher education", only in Portuguese searching the Google Academic search base. Therefore, this expressions were chosen because it is considered accessible and accessible. From this recovery came a documental large amount, which was refined by means of exclusion criteria in five stages, resulting in the end in fifteen articles. Although there are public policies that seek to make direct access to these students in higher education, their analysis showed gaps between the guidelines and the reality, leading to the lack of commitment to the impediment, when dealing with the permanence and effective completion of the training. It is a pressing concern to implement and compliance with legislation that ensures accessibility, so that this scenario reverts and the right to education is actually accessible.